Strong influence of the oxygen stoichiometry on the vortex bundle size and critical current densities J c of GdBa2Cu3Ox -coated conductors grown by co-evaporation - Haberkorn, N. (2017)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas